The impact of a weakened AMOC on European heatwaves - Virna L Meccia; Claudia Simolo; Katinka Bellomo; Susanna Corti (Environmental Research Letters)
In our changing climate we expect an increase in the frequency of heatwaves, which are extreme events that can have severe consequences for human health, ecosystems, and economies. In this study, we examine how the weakening of the atlantic meridional overturning circulation (AMOC) may influence the occurrence of extreme warm events in Europe. Our analysis is based on a series of numerical experiments conducted using the EC-Earth3 climate model, which includes three ensembles of 20 Atmospheric Model Intercomparison Project-like members. The large ensemble size makes these simulations well-suited to studying rare extreme events. Our findings reveal that during boreal summer, the Northern hemisphere (NH) experiences overall mean cooling, most pronounced in the North Atlantic region. Therefore, the extreme warm events in Europe identified by using a fixed threshold tend to be less frequent. However, the cooling pattern reduces the meridional gradient of near-surface air temperature at high latitudes of the NH. As a result, the speed of the summer jet stream decreases, while the frequency of Ural atmospheric blocking events increases. Atmospheric blocking in summer is closely linked to heatwaves, primarily through subsidence warming and enhanced downward shortwave radiation under clear sky conditions. Consequently, the weakening of the AMOC leads to an increased frequency of heatwaves in Eastern Europe, the only region that presents this opposite trend. This study highlights the significant role that three-dimensional ocean circulation plays in shaping weather patterns, including extreme events such as heatwaves in Europe. These findings have important implications for future climate projections, as the AMOC is expected to weaken by the end of this century. Thus, as the Earth continues to warm, we may face an increased risk of heatwaves due to the combined effects of global warming and a weakening AMOC.